Focusing Telescopes in Nuclear Astrophysics - Ballmoos, Peter (Springer Netherlands : Imprint: Springer, 2006)
This volume is the first of its kind on focusing gamma-ray telescopes. Forty-eight refereed papers provide a comprehensive overview of the scientific potential and technical challenges of this nascent tool for nuclear astrophysics. The book features articles dealing with pivotal technologies such as grazing incident mirrors, multilayer coatings, Laue- and Fresnel-lenses - and even an optic using the curvature of space-time. The volume also presents an overview of detectors matching the ambitious objectives of gamma ray optics, and facilities for operating such systems on the ground and in space. The extraordinary scientific potential of focusing gamma-ray telescopes for the study of the most powerful sources and the most violent events in the Universe is emphasized in a series of introductory articles. Practicing professionals, and students interested in experimental high-energy astrophysics, will find this book a useful reference.